Evaluation of heat transfer and exergy loss in a concentric double pipe exchanger equipped with helical wires - Akpinar, Ebru Kavak (Pergamon-Elsevier Science Ltd, 2006)
In this study, the effects on heat transfer, friction factor and dimensionless exergy loss were investigated experimentally by mounting helical (spring shaped) wires of different pitch in the inner pipe in a double pipe heat exchanger. In the experiments, hot (air) and cold (water) fluids flowed through the inner pipe and annulus, respectively. The experiments were performed for both parallel and counter current flow modes of the fluids at Reynolds numbers between 6500 and 13,000. An augmentation of up to 2.64 times in Nusselt number compared to the empty pipe was obtained in the helical system. The increase in friction factor was about 2.74 times that of the empty pipe, depending on Reynolds number and the pitch or helical number. An augmentation of up to 1.16 times in the dimensionless exergy loss compared to the empty pipe was obtained in the helical system. Some empirical correlations expressing the results were also derived and discussed. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: concentric double pipe heat exchanger; helical wires; heat transfer; exergy loss; friction factor